Fano effect of a laterally coupled vertical triple quantum dot system - 贺泽龙 吕天全 张迪 (Chinese physics B, 2013)
Using the nonequilibrium Green＇s function technique,electron transport through a laterally coupled vertical triple quantum dot is investigated.The conductance as a function of electron energy is numerically calculated.The evolution of the conductance strongly depends on the configuration of dot levels and interdot coupling strengths.